PENGARUH KEMASAN, BRAND IMAGE DAN BRAND TRUST TERHADAP MINAT BELI KONSUMEN PADA PRODUK PANCAKE DURIAN SHARIE RADJANYA DI KOTA MATARAM - adiahsari lidyasuwanti (Master of Management, Mataram University, 2017)
This study examines the various aspects of marketing that will impact the future increase in sales results in the development of Micro Small Medium Enterprises (UMKM) in business durian pancake products. The purpose of this study is to determine the effect of packaging, brand image and brand trust will be known to the community members who already know and recognize products Pancake Durian. This study focused on durian pancake products with brand Sharie Radja in Mataram. Researchers took 100 respondents in this study that will be sampled by accidental sampling technique which is a sampling procedure to select a sample of the most easily found or accessed and refers to the opinion of Roscoe (1975) indicated he fully appropriate sample size for researchers. In even this study aided by SPSS by using multiple linear regression analysis which will determine the effect of independent variables to the dependent party.The results showed that: (1) variable packaging not significant effect on interest Buy the product Pancake Sharie Radja In Mataram. (2) The variables significantly influence the brand image of Interests Buy the product Pancake Sharie Radja In Mataram. (3) The variables significantly influence brand trust Interests Buy the product Pancake Sharie Radja In Mataram.Keywords: Packaging, Brand Image, Brand Trust, Interests Buy.